Visual Outcome after Oral versus Intravenous Methylpredisolone Therapy for Bilateral Optic Neuritis in Adults - Naima Lassie; Hartono Hartono (Universitas Baiturrahmah, 2020)
Introduction: Bilateral optic neuritis in adults is rarer then unilateral optic neuritis. The purpose of this study was to know the clinical profile and to know the visual outcome of bilateral optic neuritis in adult patients after oral versus intravenous methylprednisolone therapy. Methods: A retrospective review of patients with bilateral optic neuritis referred to dr.Sardjito General Hospital, Yogyakarta from 2011-2014. The data consisted of bilateral optic neuritis, unassociated with other pathologic processes. There are two groups of patients: Group A taking oral methylprednisolone 1mg/kgBB and Group B received intravenous methylprednisolone (as ONTT guideline). Visual acuity, visual field with Goldmann Perimetry, RAPD (Relative Afferent Puppilary Defect), Ishihara test and direct ophthalmoscopy evaluation were recorded and analysed in both group at baseline, 1 week, 1 month and 3 months follow up. Results: Nineteen women and 9 men, with age range of 18-54 years old, had bilateral optic neuritis. The majority of the patients suffered from retrobulbar neuritis (43%), papilitis (39%) and neuroretinitis (18%). The average visual acuity before treatment in Group A was 0.22 ± 0.29 and in Group B had poorer average visual acuity 0.03±0.04 (p>0.05). But the trend of visual recovery in Group B with visual acuity at baseline worsen, the recovery of visual acuity was faster and better at one week. After one month the visual acuity was comparable in both groups (p>0.05). Conclusions: Visual improvement in early period of adult bilateral optic neuritis was similar after oral and intravenous methylprednisolone therapy.